Логістика інноваційної діяльності в сучасних концепціях управління - Кабанець, Ірина Анатоліївна (НТУ "ХПІ", 2016)
Актуальність теми обумовлена зростанням ролі творчої (інноваційної) складової праці персоналу, яка в виробничому процесу змінює рух матеріального, фінансового і інформаційного потоків, що потребує використання принципу логістики в управлінні інноваційною діяльністю. Досліджується логістичний підхід до управління інноваційною діяльністю в сучасних концепціях, визначено особливості її цільової направленості. Обґрунтовується, що логістичні потоки, які пов’язані із забезпеченням інноваційної діяльності, визначають умови руху додаткового продукту в періоді робочого дня. Акцентується увага на умовному виміру руху додаткового продукту в еквіваленті потенційних коштів, і пропонується розглядати їх в якості носія інформації про економічні цілі логістики інноваційної діяльності персоналу. Подальше дослідження пов’язано з визначення механізму виміру логістики руху додаткового продукту в робочому дні та мотивації персоналу до впровадження інновацій.

Actuality of theme is conditioned by the increase of role of creative (innovative) component labor, that in productive to the process changes motion of material, financial and informative stream that needs corresponding logistic. The brought analysis over of modern conceptions of management innovative activity shows that her a logistic orientation does not take into account motion of additional product in the periods of working day. It will be that an additional product can not be examined for outside activity of man, so as he is the product of this activity, that is formed not only under the action of the personal physical and psychological possibilities of man, organizationally - technical requirements of labor but also economic relations in activity of people. Logistic streams that are related to providing of innovative activity are examined as terms of motion of the added product. Attention is accented on conditional to measuring of motion of additional product in the equivalent of potential money, and it is suggested to examine him as a transmitter of information about economic aim of logistic in activity of personnel. Further research is related to determination of mechanism of measuring of logistic of motion of the added product and his using for a management innovative activity, determination of principles of integration of logistic streams in providing of effective activity, improvement of mechanism of motivation of personnel to development and introduction of innovations.
The logistic of innovative activity is in modern conceptions of management
Keywords: інновація; додатковий продукт; потенціальні кошти; логістичні потоки; additional product; potential money